The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1371/journal.pone.0029465
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the RNASE3 Gene Are Associated with Susceptibility to Cerebral Malaria in Ghanaian Children

Abstract: BackgroundCerebral malaria (CM) is the most severe outcome of Plasmodium falciparum infection and a major cause of death in children from 2 to 4 years of age. A hospital based study in Ghana showed that P. falciparum induces eosinophilia and found a significantly higher serum level of eosinophil cationic protein (ECP) in CM patients than in uncomplicated malaria (UM) and severe malaria anemia (SA) patients. Single nucleotide polymorphisms (SNPs) have been described in the ECP encoding-gene (RNASE3) of which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 49 publications
0
35
2
Order By: Relevance
“…A severe pathology is attributed to the protein neurotoxicity, which causes cerebral malaria, a major cause of children ' s death at an early stage. The natural variant (Arg97Thr), which reduces the protein cytotoxicity ), seems to have been selected in the Ghana population exposed to malaria infection, as a mechanism to avoid the protein severe neurotoxic side effects (Adu et al , 2011 ). A similar scenario was reported for Schistosoma infection, a common helminth parasite in tropical areas.…”
Section: The Eosinophil Cationic Protein (Ecp) In Host Defencementioning
confidence: 78%
See 1 more Smart Citation
“…A severe pathology is attributed to the protein neurotoxicity, which causes cerebral malaria, a major cause of children ' s death at an early stage. The natural variant (Arg97Thr), which reduces the protein cytotoxicity ), seems to have been selected in the Ghana population exposed to malaria infection, as a mechanism to avoid the protein severe neurotoxic side effects (Adu et al , 2011 ). A similar scenario was reported for Schistosoma infection, a common helminth parasite in tropical areas.…”
Section: The Eosinophil Cationic Protein (Ecp) In Host Defencementioning
confidence: 78%
“…In fact, the proteolytic processing is used extensively in immunology cascade events. A local cleavage can release the active peptides in the infection area in the same manner as cecropin is released from cathelicidins expressed in neutrophils (Zanetti et al , 1995 ;Burton and Steel , 2009 ), lactoferricin is derived from the N-terminus (Krieg et al , 1998 ;Clark et al , 2003 ); Tyr33 nitration (Ulrich et al , 2008 ) Host defense against viral infections; chemotaxis for dendritic cells (Rosenberg , 2008a ) RNase 3 (tested against several Gram-negative and -positive species (Torrent et al , 2009b(Torrent et al , , 2011b Arg97/Thr (related to asthma propensity and disease-induced pathologies) (Eriksson et al, 2007a;Adu et al , 2011 ) Gly103Arg 3 potential N-glycosylation sites; 10 purifi ed variants of N-linked glycosylated forms (Eriksson et al , 2007b ); N-glycosylation processed upon secretion by activated eosinophils (Woschnagg et al , 2009 );…”
Section: Introduction: Antimicrobial Rnasesmentioning
confidence: 99%
“…In addition, another study demonstrated that ECP can suppress the growth of Pf in in vitro [ 22 ]. Above findings led to several genetic studies of the RNASE 3 gene in African populations [ 19 , 20 ], which all showed an association between RNASE 3 polymorphisms (+ 371C > G and + 499G > C) and SM [ 19 , 20 ], further confirming its role in severity of the disease. The minor allele frequencies of + 371C > G and + 499G > C polymorphisms were more than 0.20 in African populations [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 90%
“…Similarly, among host genes, polymorphisms in intercellular adhesion molecule 1 (ICAM-1), cluster of differentiation 36 (CD36), tumor necrosis factor-alpha (TNF-α), Interferon-gamma (IFN-γ), interleukin-1β, complement receptor-1 (CR-1), ATP binding cassette subfamily B member 1 (ABCB1) and adenosine A2a receptor (ADORA2A) have linked to the development of SM [ 9 16 ]. Ribonuclease 3 ( RNASE 3 ), which encodes eosinophil cationic protein (ECP), an important protein produced by eosinophils during inflammation and infection [ 17 , 18 ], was found to increase susceptibility to SM [ 19 22 ]. Indeed, SM patients had higher ECP levels and hypereosinophilia compared to UM patients [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an in vitro study has demonstrated that ECP could inhibit P. falciparum growth in a dose-dependent manner (Waters et al, 1987). Based on the evidence that ECP might be important in the control of P. falciparum infection, but may also play a role in CM pathogenesis, Adu et al (2011) investigated the association between polymorphisms in RNASE3 and susceptibility to CM in a hospital-based malaria study involving CM, SA, and UM patients. During the analysis of the c.371G.C polymorphism [rs2073342; 434(G > C)], results showed that the 371G allele was associated with susceptibility to CM and forms part of a risk-associated haplotype GGA defined by the markers: rs2073342 (G-allele), rs2233860 (G-allele), and rs8019343 (Aallele), respectively.…”
Section: Genetic Featuresmentioning
confidence: 99%